The neutral and nearly neutral theories of molecular evolution 2 - Bielawski, Joseph P. (Henry Stewart Talks, 2022)
Nearly neutral model, Distribution of fitness effects of new mutations, Predictions of Neutral Theory, Evolutionary implications of nearly neutral evolution, Protein stability as an example of evolutionary dynamics